Neutron excess number and nucleosynthesis of heavy elements in a type Ia supernova explosion - Panov, I. V.; Korneev, I. Y.; Blinnikov, S. I.; Röpke, Friedrich (JETP letters, 2016)
Type Ia supernovae produce very powerful burst of light, which can be observed to high redshift. This fact is very attractive for cosmological applications. For supernova light curve modeling, it is very important to know the amount of Fe and Ni, formed during the explosion. In this paper, we explore both the chemical composition of the ejected supernova shells and the possibility of weak r-process under increased neutron excess number based on a set of trajectories of tracer particles, calculated in a hydrodynamic model of SNIa explosion. It is shown that no r-process elements are synthesized in the considered supernova model, even for an increased neutron excess number (Ye∼ 0.4) because of the slow evolution of temperature and density along chosen trajectories. The results of explosive nucleosynthesis are discussed.
Gesehen am 27.10.2020